If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-43-4i=3(1-9i)
We move all terms to the left:
-43-4i-(3(1-9i))=0
We add all the numbers together, and all the variables
-4i-(3(-9i+1))-43=0
We calculate terms in parentheses: -(3(-9i+1)), so:We get rid of parentheses
3(-9i+1)
We multiply parentheses
-27i+3
Back to the equation:
-(-27i+3)
-4i+27i-3-43=0
We add all the numbers together, and all the variables
23i-46=0
We move all terms containing i to the left, all other terms to the right
23i=46
i=46/23
i=2
| 3^2-4*3+8a=9 | | 50+9x-4=132 | | X+(x+6=20 | | 112+18m=382 | | 33n-128=400 | | 27^2^x=3^-^6 | | 225=-15m | | 3x/4-7/3=17/12 | | 0.1x-34°=90 | | -15x-14=119 | | x2–9=27 | | 2p-6=8+5 | | 9a-10=0 | | x+8/8+6=10 | | 14x-9=8x+9 | | 30=-2.9x | | x+4.1/3=5 | | 8x–6=50 | | -8x–8=-48 | | 2x^2-36x+176=0 | | (0.5x=-74)° | | x7=315 | | 2x^2=36x+176 | | b/–8=–9 | | c-20=-35 | | 10/n+7=9 | | 255=17r | | 9x+11-3x=72 | | w+1/2=1/4 | | -2x-20=80 | | -15a=-25 | | 26+x÷17=-42 |